Fracture resistance of different Post-Core systems: An In vitro study - Srivalli Podili; Rahul Puthenkandathil; Manisha M Kulkarni; Mohammed A Alobaid; Bhanu P Valluri; Zaheer A Shaik (Wolters Kluwer Medknow Publications, 2023)
Reasons for the failed endodontic teeth which had an extensive restoration can be attributed to the multiple materials that were used in it. Various post-core materials that are commonly used are compared for fracture resistance in the current study. Fourty maxillary incisors that needed root canal therapy were allocated into four groups of 10 each. Using adhesive resin cement, teeth were repaired in three experimental groups with ceramic fiber post, glass post, and stainless steel post. All these posts with composite post and core. Samples that still had their coronal structure were considered as controls that were without any post-cores. Every sample was ready for the best abutment preparation. Using the universal testing machine, all the specimens were examined for the compressive strength at 130° until fracture was experienced. The data for the force levels at which the fracture occurred were noted and compared for significance using analysis of variance (ANOVA), keeping P < 0.05 as significant. The fracture resistance values were significantly variable among all the groups, with P < 0.05. The stainless steel post exhibited the highest strength before it succumbed to the fracture. The glass posts showed better restorability and were esthetically acceptable. The least fracture resistance was demonstrated by teeth that had no post-core, highlighting the necessity of strengthening the tooth. Among all the experimental groups, the one that demonstrated the highest fracture resistance was composite core and steel posts.